2001
DOI: 10.1017/s0033291701003257
|View full text |Cite
|
Sign up to set email alerts
|

Depression, APOE genotype and subjective memory impairment: a cross-sectional study in an African-Caribbean population

Abstract: Background. Subjective memory impairment (SMI) is common in older populations but its aetiology and clinical significance is uncertain. Depression has been reported to be strongly associated with SMI. Associations with objective cognitive impairment are less clear cut. Other factors suggested to be associated with SMI include poor physical health and the apolipoprotein E (APOE) ε4 allele. Studies of SMI have been predominantly confined to white Caucasian populations.Method. A community study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 18 publications
10
66
0
3
Order By: Relevance
“…The significant relationship observed between PiB uptake and subjective cognition measured with general memory self-reports relative to age-equivalent peers echoes previous studies showing that memory complaints in healthy people were related to genetic risks[25]and brain structural and functional features of AD[18,22]. In reference to the biomarker cascade model of AD proposed by Jack et al[11]Aβ deposition measure in cognitively intact older subjects may be the most appropriate measure to detect the earliest manifestation of AD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The significant relationship observed between PiB uptake and subjective cognition measured with general memory self-reports relative to age-equivalent peers echoes previous studies showing that memory complaints in healthy people were related to genetic risks[25]and brain structural and functional features of AD[18,22]. In reference to the biomarker cascade model of AD proposed by Jack et al[11]Aβ deposition measure in cognitively intact older subjects may be the most appropriate measure to detect the earliest manifestation of AD.…”
Section: Discussionsupporting
confidence: 80%
“…Although the present study did not specifically recruit SCI subjects, previous work in SCI has shown brain structural and functional abnormalities that mimic those commonly observed in AD (i.e. decreased grey matter volume[1621], cerebral metabolism reduction[22,23]), as well as increased genetic risk for AD (such as apolipoprotein E ε4 allele[24,25]). Furthermore, postmortem studies have consistently observed that memory complaints in healthy older adults were associated with amyloid in autopsied tissues at death[26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Among those with LOAD, the estimated APOE4 allele frequency is 0.423 (versus 0.128 among the cognitive controls) and is strongly associated with LOAD (p<0.001) as has been replicated many times in previous studies (Table 3). To be consistent with other studies [5,6,9,17,21,23,27,30,35] we also tested genotypes based on presence or absence of the APOE4 allele and found strong association between carriers and LOAD (OR=6.5; p<0.001; Table 3). …”
Section: Resultssupporting
confidence: 86%
“…However, in addition to LOAD, APOE4 has been implicated as a risk factor for several neuropsychiatric disorders including LOD. At least nine studies have reported an association between APOE4 and depressive phenomenology (Table 1) [4,6,9,16,25,27,29,30,35]. While there are positive studies demonstrating association between APOE4 and depression in the elderly, there are also negative reports [7,8, 11,12,17,18,2023,37,39].…”
Section: Introductionmentioning
confidence: 99%
“…SCC have been found to predict accelerated memory decline [6], increased risk of AD [79], and have been associated with the presence of neurobiological markers of AD (eg, grey matter atrophy [1014], white matter integrity [15], amyloid burden [16, 17] and AD pathology at autopsy [18]). Although APOE ε4 has been associated with a greater prevalence of SCC [1921], very limited research has addressed whether SCC predict memory decline in APOE ε4 carriers [22]. …”
Section: Introductionmentioning
confidence: 99%